Economics of Custom Hiring of Combine Harvesters in North-Western Indo-Gangetic Plains of India - A Case Study - Thakur, T C; Khura, Tapan Kumar; Kishor, Raj; Amdekar, S J (Journal of Agricultural Engineering, 2004)
Combine harvesters were introduced in the North-Western Indo-Gangetic plains of India due to labour shortage particularly on harvesting season and uncertain weather conditions. Now, these are being popularized and adopted by all categories of farmers. The custom unit managers who are involved in the business were selected for this study, which was conducted in 7 districts of North-Western plains of U.P. and one district of Tarai region of Uttaranchal during the year 2001-02. The North-Western Indo-Gangetic Plains were classified in three intensity zones based on crop harvesting index i.e. high intensity zone (greater than 60%), medium intensity zone (30-60%) and) low intensity zone (less than 30%). A total of 30-unit managers (10 unit managers from each intensity zone) were selected randomly for the present study. The data were collected from these selected unit managers/owners on a pre-structured and well-tested proforma. About 90% of combine harvesters on the farms were of local made. The area of coverage of combine harvester was about l49.81ha in Kharif season and 261.81ha in Rabi season. The field capacity of commercial combine was 0.86 ha/h in Rabi season and 0.66 ha/h in Kharif season. Combine owners reported that the business of combines on custom hiring had become highly competitive.